Mating-related behaviour of grizzly bears inhabiting marginal habitat at the periphery of their North American range - Edwards, Mark A.; Derocher, Andrew E. (Behavioural processes, 2015)
•We test the roam-to-mate hypothesis for a peripheral population of grizzly bears.•Our results contradict the roam-to-mate hypothesis for this peripheral population.•Finding quality food may take precedence over mate-searching in marginal landscapes.•Once found, mate sequestering may be advantageous for this low-density population.•Differences in mating system may reflect local adaptations to marginal conditions. In comparison to core populations, peripheral populations have low density and recruitment, and are subject to different selective pressures, such as environmental conditions, food type and availability, predation, disease, etc., which may result in behavioural modifications to mating. We test the roam-to-mate hypothesis for a peripheral population of grizzly bears (Ursus arctos) at the northern extent of their North American range, in Canada's Arctic. If bears are roaming-to-mate, we predicted greater range size and daily displacement, and more linear movements for receptive animals during the mating period compared to post-mating. In contrast to our predictions, we found that in general range size and displacement increased from mating to post-mating regardless of reproductive status. When considered across both periods, females with cubs-of-the-year had smaller range use metrics than other reproductive groups, which we attribute to a counter-strategy against sexually selected infanticide and the reduced mobility of cubs. Linearity of movements remained near zero during both periods across all groups, suggesting tortuous movements more characteristic of foraging than of mate-searching. We suggest that for this population, finding quality habitat takes precedence over mate-searching in this marginal Arctic landscape. Alternatively, a more monogamous mating system and sequestering behaviour may have obscured movement differences between the two periods. The behavioural differences in mating that we observed from what is typical of core populations may reflect local adaptation to marginal conditions and could benefit the species in the face of ongoing environmental change.